HISTOPATHOLOGICAL EFFECT OF DIPLOSTOMUM INFECTION ON GILLS OF HETEROPNEUTES FOSSILIS (BLOCH) - ALAM, M. MANSOOR; DUBEY, N.K.; KUMARI, USHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
[Text Box: publish ;onomic d bear a e of the y words SULTS, ever, be ide. It is journal. pace, on CD or e-;END of ferences ne paper ire to be implete" I List of on white be used] Parasites thrive primarily in a dynamic equilibrium with their host(s) and they are 'often overlooked in fish health assessments. The damage associated with the fish host is relative to the intensity of infection and severity of infestation of parasites. Infection with the parasite Dip/ostonnun metacercariae lead to severe gill (branchial) pathlogy and may result in host mortality.